Penerapan Metode Design Thinking dalam Perancangan UI/UX Website CV. Lokal Industri - Ramadhan, Naafi'; Febrita, Ruth Ema; Prasetyo, Junaedi Adi (STMIK Banjarbaru, 2024)
This study focuses on designing the User Interface (UI) and User Experience (UX) for a web-based ordering system at CV. Lokal Industri in Banyuwangi, and evaluating the developed prototype. The company faces operational challenges due to manual ordering processes that are susceptible to cancellations. By employing the design thinking method, which encompasses the stages of empathize, define, ideate, prototype, and testing, the research seeks to understand user needs and develop an intuitive and functional design. The design system incorporates consistent UI elements like vivid red, black, and white colors, Montserrat font, and Font Awesome icons, ensuring good contrast, readability, and reinforcing brand identity. The results demonstrate a successful design, with a 100% success rate in usability testing and an average System Usability Scale (SUS) score of 95, reflecting very high user satisfaction. This approach effectively meets user needs, enhances operational efficiency, and provides a positive user experience.Keywords: Design thinking; UI/UX design; Web-based ordering system; Usability testing; User experience.AbstrakPenelitian ini bertujuan untuk mengembangkan antarmuka pengguna (UI) dan pengalaman pengguna (UX) sistem informasi pemesanan konveksi berbasis web pada CV. Lokal Industri di Banyuwangi dan menguji prototipe yang dikembangkan. CV. Lokal Industri mengalami kendala operasional akibat proses pemesanan manual yang rentan dibatalkan. Metode design thinking diterapkan melalui tahap empathize, define, ideate, prototype, dan testing, untuk memahami kebutuhan pengguna dan menciptakan desain yang intuitif dan fungsional. Desain sistem melibatkan komponen UI konsisten, seperti warna vivid red, hitam, putih, font Montserrat, dan icon Font Awesome, untuk memastikan kontras dan keterbacaan serta memperkuat identitas merek. Hasil penelitian menunjukkan keberhasilan desain dengan tingkat keberhasilan usability test 100% dan skor rata-rata System Usability Scale (SUS) sebesar 95, menunjukkan kepuasan pengguna yang sangat tinggi. Pendekatan ini berhasil memenuhi kebutuhan pengguna, meningkatkan efisiensi operasional, dan memberikan pengalaman yang positif.Â